2021
DOI: 10.32322/jhsm.900023
|View full text |Cite
|
Sign up to set email alerts
|

Does red ginseng ameliorate liver damage caused by obstructive jaundice? : an experimental study

Abstract: Aim: This experimental study aimed to evaluate the hepatoprotective effect on obstructive jaundice (OJ) of oral Red Ginseng (RG) extract, which is known to have anti-inflammatory and antioxidant properties. Material and Method: The rats were randomly separated into 3 groups of 10 rats: The sham group, the control group, and the treatment group. In Group 1 (sham), the common bile duct (CBD) was identified but no ligation or transection was performed. In Group 2 (control), the CBD was identified and ligation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Durhan et al created a mechanical icterus model in rats and demonstrated the anti-inflammatory and antioxidant effects of RG. In their study, they showed that RG significantly decreased MDA values, which indicates intracellular oxidative stress, and significantly increased the level of catalase, which is an important antioxidant [31]. Another study showing the antioxidant effect of RG is the study of Cho et al They showed that the use of RG in lung injury caused by mechanical ventilation in rats significantly decreased MDA values [32].…”
Section: Discussionmentioning
confidence: 95%
“…Durhan et al created a mechanical icterus model in rats and demonstrated the anti-inflammatory and antioxidant effects of RG. In their study, they showed that RG significantly decreased MDA values, which indicates intracellular oxidative stress, and significantly increased the level of catalase, which is an important antioxidant [31]. Another study showing the antioxidant effect of RG is the study of Cho et al They showed that the use of RG in lung injury caused by mechanical ventilation in rats significantly decreased MDA values [32].…”
Section: Discussionmentioning
confidence: 95%
“…Considering the mechanism of action of ginsenosides, anti-inflammatory effects have been proven by purifying ginsenosides. Expressions of pro-inflammatory cytokines (TNF-alpha, IL-1 and IL-6) have been shown to induce M1 and M2 polarization of macrophages or microglia while inhibiting iNOS and COX-2 enzyme expressions, which was found to be the anti-inflammatory mechanism of ginsenosides [17]. In a study by Kosmaz et al, red ginseng was given to rats that underwent splenectomy, and its antioxidant and anti-inflammatory activity was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, red ginseng was shown to have significantly reduced MDA values, which indicate intracellular oxidative stress, and significantly increased the level of catalase, an important antioxidant [18]. In another study by Durhan et al, in which oral red ginseng was evaluated in experimental occlusive jaundice, it was observed that MDA value decreased and catalase value increased [17]. However, in the current study, MDA value decreased and catalase value increased, but no statistically significant difference was observed between the control and red ginseng groups.…”
Section: Discussionmentioning
confidence: 99%